Motivation in Islamic Education: An Integrative Analysis of Motivational Hadiths with Modern Educational Psychology Theory - Ihsan, Muhammad Aufa; Thalib, Abdurrahman; Nazrin, Marina (Journal of Education Method and Learning Strategy, 2026)
This study aims to integrate motivational hadiths with modern educational motivation theories to create a more comprehensive motivational model in the context of Islamic education. The method used is library research with content analysis and comparative analysis of hadith texts in Al-Lu’lu’ wal Marjan and contemporary motivational theories. The results of the study indicate that the motivational messages in the hadiths such as patience in the first test, sincerity in good deeds, the process of training in developing patience and the importance of small deeds, have a strong alignment with the theories of Growth Mindset, Grit Theory, Self-Determination Theory, and Expectancy-Value Theory. All the hadiths studied have the status of muttafaqun alaih so that they have high normative legitimacy as a theoretical basis. These findings show that spiritual values in the hadiths can strengthen modern psychological explanations and provide answers to the need for a motivational model that combines transcendental dimensions with empirical dimensions. This study concludes that this integration produces a more complete motivational framework and has the potential to improve the quality of Islamic education by developing students with more character, resilience, and strong intrinsic motivation.